Linoleic acid in diets of mice increases total endocannabinoid levels in bowel and liver: modification by dietary glucose - S. Ghosh; J. F. O'Connell; O. D. Carlson; I. González‐Mariscal; Y. Kim; R. Moaddel; P. Ghosh; J. M. Egan (Obesity Science & Practice, 2019)
Summary Aim Linoleic acid (LA) is an essential fatty acid involved in the biosynthesis of arachidonic acid and prostaglandins. LA is known to induce obesity and insulin resistance. In this study, two concentrations of LA with or without added glucose (G) were fed to mice to investigate their effects on endocannabinoid (EC) biology. Materials and Methods Four groups of C57BL/6 mice were provided with diets containing 1% or 8% LA with or without added G (LAG) for 8 weeks. Body weights, food intake, circulating glucose and insulin levels were measured throughout the study. Following euthanasia, plasma, bowel and hepatic ECs, monoacylglycerol lipase and fatty acid amide hydroxylase protein levels (enzymes responsible for EC degradation) and transcriptional activity of PPARα in liver were quantified. Liver was probed for evidence of insulin receptor activity perturbation. Results Increasing dietary LA from 1% to 8% significantly increased circulating, small bowel and hepatic ECs. 1%LAG fed mice had lowest feed efficiency, and only liver levels of both ECs were reduced by addition of G. Addition of G to 1% LA diets resulted in elevated monoacylglycerol lipase and fatty acid amide hydroxylase protein levels (p < 0.001 and p < 0.001, respectively) in liver due to increased transcriptional activity of PPARα (p < 0.05). The reduced EC levels with addition of G also correlated with a measure of enhanced insulin action. Conclusion In conclusion, body weight of mice is influenced by the source of calorie intake. Furthermore, tissue EC/g are dependent on tissue‐specific synthesis and degradation that are modulated by dietary LA and G which also influence food efficiency, and down‐stream insulin signalling pathways. The findings could potentially be useful information for weight management efforts in humans.